An Overview of the Biology, Epidemiology and Control of Uncinula necator (Powdery Mildew) on Grapevine, with Ref ere nee to South Africa - Halleen, F.; Holz, G. (South African Journal of Enology and Viticulture, 2017)
Grape powdery mildew, caused by Uncinula necator, is the most widespread and destructive disease of grapevine.  The disease can be found in most grape-growing areas of the world, including the tropics. In South Africa, grape powdery mildew was first reported in 1880, and since then has become the most important disease of grapevine.  The disease can effect all phases of plant growth, and without necessarily causing obvious symptoms, may have a harmful effect on the vine and its products. The pathogen follows a specific pattern in each part of the world to create an epidemic. This pattern is determined by biological characteristics of the organism, climatic factors, cultivation practices and cultivar choices.  Increased world-wide emphasis on the production of disease-free grapes with minimal fungicide input provides a sound reason for exploring more efficient disease management strategies through a better understanding of U. necator epidemiology and population genetics. Knowledge of these aspects is available for various parts of the world, but little is known about its relevance to South African vineyards. In this article a South African perspective of the pathogen and its control is outlined, based on recent local findings, and considered in the light of knowledge available in other parts of the world.